CHALLENGES OF PASSIVE COOLING TECHNIQUES IN BUILDINGS: A CRITICAL REVIEW FOR IDENTIFYING THE RESILIENT TECHNIQUE (Jurnal Teknologi (Sciences & Engineering), 2016)
Although many studies have investigated the potential of passive cooling technologies in hot and arid areas, an important question remains. Why did architects ignore the passive cooling technologies in new buildings despite their sustainability? This study is based on this pivotal question. This study aims to review and explore the impediments that undermine the use of these technologies in hot, arid areas; moreover it intends to determine the most resilient passive cooling technique which may be used as a master technique in buildings by architects. The study focuses on twelve of a proposed passive technologies. These techniques are reviewed according to their potentials and challenges. Hence, the drawbacks of each passive technique will be identified in order to recognize the most resilient passive technology. This study suggests that spatial limitations are the most salient challenges facing architects when they attempt to utilize passive cooling technologies. This study also concludes that the openings created in the upper parts of external walls is the most flexible technique that can be implemented in new and existing buildings, without any of the aforementioned impediments.Â